2010
DOI: 10.1016/j.polymertesting.2010.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Parametric study of crushing parameters and failure patterns of pultruded composite tubes using cohesive elements and seam, Part I: Central delamination and triggering modelling

Abstract: Typically, most of the brittle composite tubes exhibit circumferential delamination, lamina bending, axial cracking and brittle fracturing when subjected to static and dynamic loading conditions. In this work, a new innovative approach was adopted to model the above said failure modes using cohesive elements under an axial impact loading case. The circular and square cross sectional pultruded profiles made of glass-polyester were considered for the study. A numerical parametric study has been conducted to stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 27 publications
(64 reference statements)
0
29
0
Order By: Relevance
“…Fiber failures can also be modeled by cohesive elements. In a series of articles, Bouvet et al [199,[232][233][234] use cohesive elements to High velocity impact [201,275,372,373] Soft impact [202,[254][255][256] Crushing tube [203,326] Crushing plate [349,350] Energy absorbing structures [338,339,374] predict both intraply and interlaminar damage during low velocity impacts. This approach was also used to study the compression after impact behavior of laminates [235].…”
Section: Low Velocity Impactsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fiber failures can also be modeled by cohesive elements. In a series of articles, Bouvet et al [199,[232][233][234] use cohesive elements to High velocity impact [201,275,372,373] Soft impact [202,[254][255][256] Crushing tube [203,326] Crushing plate [349,350] Energy absorbing structures [338,339,374] predict both intraply and interlaminar damage during low velocity impacts. This approach was also used to study the compression after impact behavior of laminates [235].…”
Section: Low Velocity Impactsmentioning
confidence: 99%
“…With the ''stacked shell'' approach several plies or sublaminates are each modeled by shell elements connected by cohesive elements to allow for delaminations. Palanivelu et al [203,326] study the crushing of circular and square tubes using the Abaqus finite element software with a bilinear cohesive law and claim to be the firsts to use cohesive elements for this problem [326]. With the stacked-shell approach, ply interfaces can also be modeled using one-dimensional cohesive elements [327] or ''tie breaks'' in LS-DYNA [328][329][330][331].…”
Section: Automotive Applicationsmentioning
confidence: 99%
“…At the same time, the research scholars had done a lot of researches of composite aircraft structures with the combination methods of test and simulation with varying degrees of success, for circular tubes (13,14) , square tubes (15)(16)(17) , C channels (18) , corrugated composite plates (4) and fuselage section (3,6,(19)(20)(21)(22)(23)(24) . Carruthers et al suggested that the closed-section tubes had evident effects on the crush performance.…”
Section: Introductionmentioning
confidence: 99%
“…Pinho et al [11], Palanivelu et al [12] and Fleming [13] proposed various numerical models for the crushing simulation of fibre-reinforced composite materials. Sokolinsky et al [14] investigated a corrugated carbon-epoxy fabric composite plate subjected to quasi-static crushing, where intralaminar failure was simulated using an in-plane constitutive model and delamination was modelled by cohesive surface contact.…”
Section: Introductionmentioning
confidence: 99%